KECERDASAN BUATAN DALAM PENGELOLAAN PASIEN COVID-19 - Loso Judijanto; Entin Solihah (CV. ADIBA AISHA AMIRA, 2026)
Artificial intelligence (AI) has become a significant tool in the management of COVID-19 patients, with applications ranging from initial diagnosis, disease progression monitoring, to hospital logistics management. Machine learning and deep learning technologies have enabled rapid and accurate analysis of radiological images and patient data, while AI predictive applications facilitate more personalised and eflective treatment planning. However, the application of AI in this context is faced with challenges such as data privacy, information security, and integration with existing health systems. While oflering great potential, the use of AI must be carefully regulated to ensure its safe and ethical use, as well as its acceptance by medical personnel and the public.